Factors Related to Obstructive Sleep Apnea in Patients with Heart Failure and Atrial Fibrillation - Masyab, Nadiah; Lubis , Anggia Chairuddin; Raynaldo , Abdul Halim (Journal of Society Medicine, 2025)
Introduction: Obstructive sleep apnea (OSA) causes cardiovascular disturbances due to intermittent hypoxia, oxidative stress, systemic inflammation, excessive negative intrathoracic pressure, sympathetic activation, and increased blood pressure. These factors can impair myocardial contractility, leading to the development of heart failure and atrial fibrillation (AF). Epidemiological studies have shown a significant independent association between OSA, heart failure, and AF. This study aims to identify factors associated with obstructive sleep apnea (OSA) in patients with heart failure accompanied by atrial fibrillation. Method: This study was conducted on patients diagnosed with heart failure and atrial fibrillation hospitalized at the Integrated Heart Center of Adam Malik Hospital. Data collection began in August 2023 and continued until the required sample size was reached. This is an observational analytic study with a cross-sectional design. Results: A total of 51 patients participated in this study. The majority of respondents were male (66.7%), with most being aged between 60-69 years. The study found that the degree of OSA in heart failure patients with AF was predominantly mild (30.8%), followed by moderate (25.0%) and severe (17.3%). The average AHI value was 16.78 with a standard deviation of 14.359. Multivariate analysis identified two significant variables: smoking history and functional capacity (NYHA Class) (p > 0.05). Conclusion: A significant association was found between gender and smoking history with the occurrence of OSA in patients with heart failure and atrial fibrillation. The multivariate analysis also highlighted the significance of smoking history and functional capacity (NYHA Class) (p > 0.05).